A novel image encryption scheme combing optical chaos scrambling, DNA diffusion strategy and MOPSO algorithm - Xiao, Tao; Li, Qiliang; Bai, Haoruo (Optical and quantum electronics, 2024)
A secure encryption scheme, combining multi-objective particle swarm optimization (MOPSO), optical chaos, and DNA algorithm is proposed and demonstrated. In this paper, a secure encryption and decryption architecture based on optical chaotic synchronization system with injection-locking is analyzed. We prove that a main laser (ML) can drive two-pair secondary lasers (TPSLs) to generate the synchronized optical chaos with high complexity. The system employs the XOR operation between the Hash value of the initial image and optimized value by MOPSO, which modulates the bias current of ML, thus TPSLs are driven to generate two pair synchronized chaotic sequences, which combine the Hash value of the initial image to generate two keys through a certain algorithm. Furthermore, two keys are used to scramble the pixel positions of the image and diffuse image pixels through DNA rules, and then in receiving end, two same keys are used to unscramble and reversely diffuse the encrypted image. Besides modulating the bias current of ML, the other aim of MOPSO is to optimize the entropy of the encrypted image and the correlation between the adjacent pixels. In order to ensure the recovery of real image, we compute and compare the digest-message of two pair synchronized chaotic sequences by using Hash algorithm in two ends before transmitting the encrypted image over optical fiber link. By synchronizing with the lasers at the sending end, we obtained two same keys to decrypt the ciphertext image in the receiving end. The simulation results show that this scheme can achieve secure communication of image against various attacks by analyzing and testing the security of the encrypted image.